Review of 1972/01/29 Concert at Birmingham and Midland Institute. The Chasm: Judith Jones (soprano), Simon Desorgher (flute), Peter Lawson (piano) - Bracefield, Hilary (Contact: A Journal for Contemporary Music (1971-1990), 1972)